INTERAKSI METABOLISME MANUSIA-ALAM: ENVIRONMENTAL ETHIC MASYARAKAT ADAT JUHU DALAM PENGELOLAAN HUTAN - Ribka Aprilia; Ismar Hamid; Sri Hidayah (Program Studi Sosiologi, FISIP ULM, 2023)
In the midst of the rise of the ruling anthropocentric disposition, there is still, a group of people who reject the disposition that symbolizes selfishness and lean more towards the disposition of ecocentrism. This study aims to find and describe the way people view and interpret their forests and discover values related to ecocentrism ethics. Data collection techniques used observation techniques, interviews and documentation, as well as focus group discussions and strengthened by secondary data from literature studies. This research is field research, with a qualitative approach. The research was carried out in Juhu Village, Batang Alai Timur District, Hulu Sungai Tengah Regency, South Kalimantan. The results showed that the people of Juhu Village have a very strong attachment to the forest where they live. Judging from various activities and activities in the form of rituals, there is always an element of respect for nature. Juhu society is very dependent on nature. A form of ecocentrism in the Juhu community, starting from local wisdom and daily activities that are considered ordinary even though they contain management values. Nowadays, people are starting to make movements to reject actions or decisions that could destroy the environment in which they live, by being more courageous to speak out. Juhu people no longer rely solely on local knowledge, they also use technology as a supporting tool. In the future, the Juhu community will be more courageous in voicing opinions and desires about sustainability values.